2020
DOI: 10.3389/fpsyg.2020.568953
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Integrity of the Hippocampus During Childhood: Relations With Age and Source Memory

Abstract: The hippocampus is a brain structure known to be important for memory. However, studies examining relations between hippocampal volume and memory across development yield mixed results. This may be due in part to the fact that volume is a coarser measure of hippocampal composition. Studies have begun to examine measures of diffusion, which capture characteristics of the microstructure of the hippocampus, and thus may provide additional information about the integrity of the underlying neural circuits. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…Gray matter MD is associated with alterations in synaptic, glial, and dendritic density and activity, such as swelling, arborization, and synaptic pruning (Blumenfeld-Katzir et al, 2011;Le Bihan, 2012;Sagi et al, 2012;Crombe et al, 2018;Stolp et al, 2018). Additionally, previous work suggests that cortical and subcortical gray matter diffusivity are stronger predictors of cognitive performance than volumetric measures across the lifespan (Kantarci et al, 2005;Jeon et al, 2012;Hong et al, 2013;Pereira et al, 2014;Weston et al, 2015;Callow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray matter MD is associated with alterations in synaptic, glial, and dendritic density and activity, such as swelling, arborization, and synaptic pruning (Blumenfeld-Katzir et al, 2011;Le Bihan, 2012;Sagi et al, 2012;Crombe et al, 2018;Stolp et al, 2018). Additionally, previous work suggests that cortical and subcortical gray matter diffusivity are stronger predictors of cognitive performance than volumetric measures across the lifespan (Kantarci et al, 2005;Jeon et al, 2012;Hong et al, 2013;Pereira et al, 2014;Weston et al, 2015;Callow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of development, gray matter MD is generally negatively associated with age and better cognitive performance and is thought to represent increased myelination and axonal and neural density (Mah et al, 2017;Fjell et al, 2019;Callow et al, 2020). Meanwhile, in older adults, age and disease progression are usually positively associated with gray matter MD, which is believed to result from a general decline in dendritic and synaptic density (Ray et al, 2006;Pereira et al, 2014;Weston et al, 2015;Salminen et al, 2016;O'Shea et al, 2016;Langnes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings may therefore suggest a higher level of hippocampal maturation in the WPC-A-EV and WPC-PL groups compared to SL. Measurements of low mean diffusivity in the hippocampus have previously been shown to correlate with better memory performance in children [72]. Moreover, mean diffusivity has been suggested to be a better predictor of hippocampal-dependent memory than volume [72].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of low mean diffusivity in the hippocampus have previously been shown to correlate with better memory performance in children [72]. Moreover, mean diffusivity has been suggested to be a better predictor of hippocampal-dependent memory than volume [72]. Studies in piglets have demonstrated positive effects of dietary MFGM intake on DTI measurements in the internal capsule [28], but not in the hippocampus at 30-31 days of age [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the development of this region, but some recent work suggests potential memory-related dissociations between children ages 4-10 and adults in perirhinal cortex activity (Benear et al, 2020). A number of studies have demonstrated developmental changes in the hippocampus (Callow et al, 2020;Daugherty et al, 2016, Daugherty et al, 2017DeMaster et al, INTRAOBJECT AND EXTRAOBJECT MEMORY BINDING 13 2014; Tang et al, 2020), which is often associated with relational or extraobject binding (Davachi, 2006;Giovanello et al, 2004;Hannula & Ranganath, 2008;Lee et al, 2020;Staresina & Davachi, 2008), and it would be useful to better understand how developmental changes in the hippocampus and perirhinal cortex relate to intraobject and extraobject binding.…”
Section: Implications For Memory Binding Developmentmentioning
confidence: 99%